Direct Observation of THF Hydrate Formation in Porous Microstructure Using Magnetic Resonance Imaging - Kaihua Xue; Jiafei Zhao; Yongchen Song; Weiguo Liu; Weihaur Lam; Yiming Zhu; Yu Liu; Chuanxiao Cheng; Di Liu (Energies, 2012)
The porous microstructure of hydrates governs the mechanical strength of the hydrate-bearing sediment. To investigate the growth law and microstructure of hydrates in porous media, the growth process of tetrahydrofuran (THF) hydrate under different concentration of THF solution is directly observed using Magnetic Resonance Imaging (MRI). The images show that the THF hydrate grows as different models under different concentration of THF solution (19%, 11.4% and 5.7% by weight) at 1 °C. When the concentration is 19% (stoichiometric molar ratio of THF/H2O = 1:17), the THF hydrate grows as cementing model. However, with the decreasing concentration of THF, the growth model transfers from cementing model to floating model. The results show that the growth of the THF hydrate was influenced by the dissolved quantity of THF in the water. The extension of the observed behavior to methane hydrate could have implications in understanding their role in seafloor and permafrost stability.